Reactive and Proactive Coping Behaviors in Russian First-Year Students: Diagnostics and Development Opportunities - Anna A. Bekhter; Alexander V. Gagarin; Olesya A. Filatova (Peoples' Friendship University of Russia (RUDN University), 2021)
The relevance of the study is determined by the role of the adaptation processes of first-year students to the university environment, which is the most important (preliminary) stage for: (a) their successful overcoming of various learning difficulties; (b) comfortable and constructive interaction with teachers and other students; and (c) search and application of adaptive behavior strategies due to new living conditions. The development of proactive coping is a key factor in the students efficient learning activity because it represents a platform for their personal growth. The aim of the study is to determine the possibilities of diagnostics and development of reactive and proactive coping behavior in first-year students. The study involved 272 first-year students at Pacific National University (including 136 students of an experimental group who sought help from the University Psychology Center in 2019 and 136 first-year volunteer students as a control group). The following methods were used for diagnostics: Proactive Coping Inventory (PCI) , adapted by E.P. Belinskaya et al., Ways of Coping Questionnaire by R. Lazarus, adapted by T.L. Kryukova et al., Hardiness Survey by Salvatore Maddi adapted by D.A. Leontyev and E.I. Rasskazova, Time Perspective Inventory (TPI) by Ph.Ge. Zimbardo, adapted by A. Syrtsova et al. and Reflexivity Diagnostics Method by A.V. Karpov. As a result, the first-year students showed low levels of developed reactive and proactive coping, high levels of social and emotional support as well as escape-avoidance, average levels of strategic planning and search for informational support, and a reduced level of reflective, predictive resource. It is shown that the search for social, emotional and informational support is the basis for constructing adaptive behavior strategies. It is confirmed that self-control and the category of the future are moderating for all types of proactive coping. The conducted cluster analysis made it possible to identify three profiles, which differ in the levels and content of reactive and proactive behavior (non-adaptive, reactive and active with a tendency to proactive). Repeated measurements show that individual and group forms of psychological intervention cause changes in the indicators of reactive-proactive coping behavior, which can be regarded as a positive dynamics in the development of behavior in students of the experimental group. Finally, a conclusion was formulated about the possibilities of using various forms of psychological support (individual counseling, trainings, and self-help groups) in optimizing the first-year students proactive coping behavior.